An Analyzing on the Students Error in Using Conditional Sentence - kustianah, kustianah; Wibowo, Ari (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2020)
In this study, the writer want to analyze the student error in using conditional sentence and involve all case in conditional sentence. The method of this research is error analysis. In this research, the researcher wishes to know how is the students of the second grade at Madrasah Tsanawiyah Muhammadiyah 04 Klamalu competence in using conditional sentence type III especially in tenses “simple past perfect tense and simple future perfect tense.” The researcher gave the test to the students without the treatment the researcher want to know just one the cause of errors about the use of conditional sentence type III “simple past perfect tense and simple future perfect tense.” The result showed that the causing error of the students in using conditional sentence are carelessness, first language using, translation, the facility of students learning like English book, the method of teaching and the students themselves. After the analysis kind of conditional sentence the writer to identification the kinds of error and persentage of students error, result of reserch are: omission the total error are 10 error, the persentage is 7, 04 %. Addition the total of error 14 error, the persentage is 9, 86%. Miss- ordering error is 80 error, the persentage is 56,34% and subtitution error is 38 error, the persentage is 26,76%. So the total of students error are 142 error and the persentage is 100%.